Publications Received (Academy of Management Review, 1998)
The article is a list of publications including: “Adventures of a Bystander,” by Peter F. Drucker; “China: The Consumer Revolution,” by Conghua Li; “Compulsory Arbitration: The Grand Experiment in Employment,” by Richard A. Bales; “Doing Business in Today's India,” by Douglas Bullis; and “A Practical Guide to Acquisitions: How to Increase Your Chances of Success,” by Denzil Rankine.